Board meetings and bank performance in Africa - Simms Mensah Kyei; Katarzyna Werner; Kingsley Opoku Appiah (Cogent Business & Management, 2022)
This study examines the relationship between a board meeting and banks performance in Africa. This paper provides insight on this question after taking into account the endogeneity of the relationship between board meetings and performance. Specifically, we use the GMM technique and a sample of 635 banks from 48 countries in Africa between 2000 to 2016 to test our hypothesis and found that more board meetings, averagely 6, reduce banks' performance in sub-Sahara Africa. In the Northern Africa context, with an average board meeting of 7.68, however, we document a positive and significant association between a board meeting and bank performance. Our result suggests that fewer board meeting enhances the shareholder value of Banks in Sub-Sahara Africa but not their counterparts in North Africa. Our paper provides insights to policymakers responsible for improving the governance mechanisms in African banks.
Keywords: G21; G34; G38; 650; African banks; board monitoring; board of directors; board process; Corporate governance